Braiding archaeology, geomorphology and indigenous knowledge to improve the understanding of local-scale coastal change - Benjamin D. Jones; Mark E. Dickson; Murray Ford; Daniel Hikuroa; Emma Ryan; Ari Carrington; Juliane Chetham (Cambridge Prisms: Coastal Futures)
Coastal landforms and associated archaeological records are at risk of erosion from a combination of rising sea levels and increasingly frequent high-intensity storms. Improved understanding of this risk can be gained by braiding archaeological and geomorphological methodologies with Indigenous knowledge. 1 In this article, archaeological, geomorphological and mātauranga (a form of Indigenous knowledge) are used to analyse a prograded Holocene foredune barrier in northern Aotearoa/New Zealand. Anthropogenic deposits within dune stratigraphy are radiocarbon-dated and used as chronological markers to constrain coastal evolution, alongside geomorphological analyses of topographic data, historical aerial photographs and satellite imagery. These investigations revealed that the barrier is eroding at a rate of 0.45 m/year. A midden in the foredune, which has been radiocarbon dated to 224–270 B.P. (95% Confidence), has been exposed by coastal erosion, confirming that the barrier is in the most eroded state it has been within the past ~300 years. Vertical stratigraphy reveals the presence of midden and palaeosol deposits capped by dune sand deposits in the foredune, indicating that vertical accretion of the foredune continued over the last ~200 years, despite the barrier now being in an eroding state. Mātauranga played a vital role in this project, as it was the coastal taiao (environmental) monitoring unit of Patuharakeke (a Māori sub-tribe) that discovered the midden. The ecological mātauranga shared also played a vital role in this project, adding experiential evidence to empirical observations. The work of local Indigenous groups, like Patuharakeke, demonstrates the active use of mātauranga, woven with Western science methods to preserve or capture the knowledge contained within archaeological sites at risk of being lost to coastal erosion. In this study, we present a method for weaving mātauranga, geomorphological and archaeological approaches to gain a deeper understanding of coastal landscape development.